2023
DOI: 10.1002/adma.202209885
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancies in Piezoelectric ZnO Twin‐Mesocrystal to Improve Peroxymonosulfate Utilization Efficiency via Piezo‐Activation for Antibiotic Ornidazole Removal

Abstract: Piezoelectric mesocrystals as defective materials have been demonstrated to possess adsorptive and catalytic properties in redox reactions. However, there is still a lack of research on the quantitative relationship between the defect concentration and the piezocatalytic performance in piezoelectric mesocrystals. Herein, twin‐hierarchical structure ZnO piezoelectric mesocrystals are taken with different oxygen‐vacancies (OVs) concentrations to quantitatively investigate the effect of defect content on the pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…Peng et al reported that the oxygen precipitation reaction of NiFe 2 O 4 was promoted by constructing oxygen defects . Controlled porous NiCo 2 O 4 as high-efficiency electrocatalysts were synthesized by Yao et al Therefore, the introduction of oxygen defects into anti-spinel materials has a wide range of applications in pollutant degradation, CO 2 reduction, hydrogen evolution, H 2 O 2 production, and other aspects. The appropriate amount of oxygen deficiency can enhance the active site, promote charge transfer, and accelerate redox reactions to increase piezoelectric catalytic activity. However, the application of spinel piezoelectric catalysts with oxygen defects has been less studied. Therefore, it is meaningful to explored if NiFe 2 O 4 (NFO) with adjustable oxygen defects becomes a potentially versatile piezoelectric catalyst among numerous anti-spinel materials.…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al reported that the oxygen precipitation reaction of NiFe 2 O 4 was promoted by constructing oxygen defects . Controlled porous NiCo 2 O 4 as high-efficiency electrocatalysts were synthesized by Yao et al Therefore, the introduction of oxygen defects into anti-spinel materials has a wide range of applications in pollutant degradation, CO 2 reduction, hydrogen evolution, H 2 O 2 production, and other aspects. The appropriate amount of oxygen deficiency can enhance the active site, promote charge transfer, and accelerate redox reactions to increase piezoelectric catalytic activity. However, the application of spinel piezoelectric catalysts with oxygen defects has been less studied. Therefore, it is meaningful to explored if NiFe 2 O 4 (NFO) with adjustable oxygen defects becomes a potentially versatile piezoelectric catalyst among numerous anti-spinel materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, the polarization curve started to show a slight difference with a further increase of the current density, possibly due to the sluggish kinetics and hindered charge transfer with TC and the intermediate products during P-EC degradation under a larger current density, leading to the reduction of catalytic activity. 44,45 Figure 4b indicates that when TC was added to the electrolyte, the overpotential of Cu 5 FeS 4 /Ni 3 S 2 @NF changed from 260 to 280 mV at the current density of 30 mA cm −2 . Meanwhile, the Tafel slopes in Figure 4c have hardly changed, revealing that the catalytic reaction kinetics has not been changed, which is also consistent with the P-EC OER.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…engineering, [121] and optimization of synthesis methods. [122] These strategies aim to improve the band alignment, the electron migration pathways and the charge separation speed.…”
Section: Water-splitting Reaction For the Oxygen Supplymentioning
confidence: 99%